Crystalline@amorphous core-shell structure of WO3@WO3-xSx established via doping strategy for enhancing magnesium ions storage performance - Shiqi Ding; Yuxin Tian; Jiankang Chen; Guofeng Wang; Bing Sun; He Lv; Lei Wang; Guicun Li; Alan Meng; Zhenjiang Li (Journal of Magnesium and Alloys)
Designing cathode possessing crystalline@amorphous core-shell structure with both active core and shell is a meaningful work for resolving the low specific capacity, unstable cycling performance and sluggish reaction kinetics issues of rechargeable magnesium batteries (RMBs) by providing more active sites as well as releasing inner stress during cycling. Herein, WO3@WO3-xSx owning crystalline@amorphous core-shell structure containing both active core and active shell is constructed successfully by introducing S into metastable WO3 structure under temperature field applying. In such structure, amorphous shell would provide continuous Mg2+ diffusion channels due to its isotropy property for most Mg2+ migrating rapidly to interface and then adsorb at ions reservoir formed by interfacial electric field for increasing specific capacity. It also makes security for stable structure of WO3@WO3-xSx by alleviating volume expansion of crystalline core WO3 during cycling to prolong cycling life. Additionally, “softer” ions S2− would weaken interaction between hard acid Mg2+ and ionic lattice to enhance Mg2+ storage kinetics. Therefore, WO3@WO3-xSx delivers the superior cycling performance (1000 cycles with 83.3%), rate capability (88.5 mAh g−1 at 1000 mA g−1) and specific capacity (about 150 mAh g−1 at 50 mA g−1), which is near 2 times higher than that of WO3. It is believed that the crystalline@amorphous core-shell structure with both active core and shell designing via doping strategy is enlightening for the development of high-performance RMBs, and such design can be extended to other energy storage devices for better electrochemical performance.